Integrated transcriptomic and metabolomic analyses of pak choi [Brassica pekinensis (Lour.) Rupr] response to combined stress of acid rain and cadmium-containing atmospheric fine particulate matter - Zha, Yan; Zhao, Bo; Qiu, Jieren; Li, Xuqing (Frontiers in Environmental Science, 2022)
Heavy metal containing atmospheric particulate matter (PM) and acid rain (AR) trigger molecular alteration in plants, perturbing metabolites and damaging plant growth. However, the molecular mechanisms of plants under AR along with Cd-containing atmospheric fine particulate matter (PM2.5-Cd) stress remain unknown. In this study, integrated transcriptomic and metabolomic analyses of pak choi (Brassica pekinensis (Lour.) Rupr) exposed to AR (pH3.5) and PM2.5-Cd (500 μg·m-3) stress were performed. Metabolomics analyses revealed that AR-Cd stress mainly affected 42 metabolic pathways, including 451 differentially expressed metabolites (DEMs). RNA-seq identified 735 common differentially expressed genes (DEGs: 557 upregulated and 178 down regulated). Further analysis found several important DEGs (transcription factors, metabolic pathways genes, and signal transduction genes), including WRKY11, WRKY53, WRKY41, MYB73, NAC062, NAC046, HSFA4A, ABCC3, CAXs, GSTs, AZFs, PODs, PME41, CYP707A2, CDPK32, etc., implying that Cd chelate sequestration into the vacuoles, the antioxidant system, cell wall biosynthesis pathway and calcium signaling play a critical role in AR damage and Cd detoxification. Conjoint revealed phenylpropanoid and flavonoid biosynthesis pathway with different metabolism patterns, including the key DEM, chlorogenic acids. The results obtained using multiple approaches provides a molecular-scale perspective on plant response to AR-Cd stress.